FRI0122 Predicting factors for disappearance of anti-mutated citrullinated vimentin antibodies in sera from patients with rheumatoid arthritis. (15th June 2017) - Ishigooka, N; Fujii, T; Kondo-Ishikawa, S; Hashimoto, M; Furu, M; Tanaka, M; Ito, H; Nakashima, R; Murakami, K; Imura, Y; Yoshifuji, H; Ohmura, K; et al.
Abstract : Background: Mutated citrullinated vimentin (MCV) is one of the important targets of anti-citrullinated protein/peptide antibodies (ACPA) and is found in synovial fluid in patients with rheumatoid arthritis (RA). Serum anti-MCV antibody (anti-MCV) titer may be better correlated with RA disease activity and radiographic progression than anti-cyclic citrullinated peptide antibody (anti-CCP) titer. Objectives: In the present study, we tried to determine the predicting factor of anti-MCV disappearance in sera from RA patients. Methods: Both anti-MCV (ORGENTEC Diagnostika, Germany) and anti-CCP (MESACUP TM -2 test CCP, MBL, Japan) in sera from 280 RA patients who met 2010 ACR/EULAR classification criteria in Kyoto University RA Management Alliance (KURAMA) cohort 2013 and 2014 were measured by ELISA. Then, we determined retrospectively the predicting factors of anti-MCV disappearance using multivariate logistic analysis. Results: In 2013 cohort, anti-MCV and anti-CCP positivities were 64.6 and 84.6%, respectively. The majority (97.8%) of anti-MCV-positive patients was also anti-CCP-positive and there was significant correlation between anti-MCV and anti-CCP titers (r=0.63, p <0.001). In 2013 baseline, there was no difference in patients' age, gender and disease duration between anti-MCV-positive (n=181, 64.6%) and -negative (n=99, 35.4%) groups. DAS28, however, was higher in anti-MCV-positive group than in -negative group (3.08±1.22 vs. 2.68±1.07, p =0.011), while anti-CCP-positive (n=237, 84.6%) and -negative (n=43, 15.4%) groups had no significant difference of DAS28. Of note, whereas anti-CCP positivity rate did not change during 2013 and 2014, anti-MCV changed to positive and to negative were recognized in 20 (=7.2%) and 41 (=14.6%, disappeared group) patients. So we next compared anti-MCV disappeared and sustained-positive groups (n=140, 50.0%). There was no difference in patients' age, gender, disease duration and DAS28 in 2013. While decrease of DAS28 from 2013 to 2014 (=ΔDAS28) in disappeared group was more apparent than that in sustained-positive group (-0.58±1.1 vs. +0.02±0.34, p =0.028). Methotorexate monotherapy was rarer in disappeared group than in sustained-positive group (26.5% vs. 53.8%, p =0.015), while continuous use of biological disease modifying antirheumatic drug (bDMARD) was more frequent in disappeared than sustained-positive group (64.7% vs. 25.2%, p <0.0001). Also serum levels of KL-6, a serum marker of interstitial lung disease, were lower in disappeared than in sustained-positive group (255±146 vs. 315±183, p =0.006). To clear the most effective factor in anti-MCV disappearance, we choose variables including anti-MCV titers in baseline, KL-6 levels, ΔDAS28 and bDMARD use, and performed multivariable analysis. Analysis showed that anti-MCV titers and bDMARD use, especially TNF inhibitor (Odds Ratio =7.2, p <0.001) were observed as the predicting factors of anti-MCV disappearance. On the other hand, no predicting factor for newly anti-MCV appearance was recognized in our cohort. Conclusions: Anti-MCV, but not anti-CCP, can be disappeared in a year by continuous bDMARD use regardless of disease activity. Disclosure of Interest: None declared